2020
DOI: 10.1111/jjns.12375
|View full text |Cite
|
Sign up to set email alerts
|

Daily life activities simulation: Improving nursing students' attitudes toward older patients

Abstract: AimThis study aims to evaluate the effects of daily life activities simulation on the attitudes of first‐year nursing students toward older adults within the scope of geriatric nursing.MethodsThe study was carried out using a pretest‐posttest, quasi‐experimental design. First‐year undergraduate students (N = 119) of a nursing faculty constituted the study sample. The students were divided into two groups as intervention and control groups. The intervention group performed the daily life activities simulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…[8][9][10] Of particular note is how simulation can be effective at changing a person's attitudes and beliefs toward certain populations. Multiple studies have indicated simulation is effective in changing students' attitudes toward older adults, 11 patients at the end of life, 12 and patients with mental health conditions. 13 Simulation may also be useful when exploring issues related to poverty.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Of particular note is how simulation can be effective at changing a person's attitudes and beliefs toward certain populations. Multiple studies have indicated simulation is effective in changing students' attitudes toward older adults, 11 patients at the end of life, 12 and patients with mental health conditions. 13 Simulation may also be useful when exploring issues related to poverty.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects were asked to answer the Kogan's Attitude towards Old People Scale (KAOP), which is a 34‐item self‐report instrument developed by Nathan Kogan in 1961 to measure attitudes toward older people 12,13 . The instrument has 17 positively and 17 negatively worded items 14 rated on a six‐point Likert‐type scale, 13 with 1 being the lowest agreement and 6 the highest agreement 11 . The general range of results for KAOP varies from 34 to 204 points, and higher scores represent more positive attitudes 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Sistematik inceleme sonucunda araştırmalar eğitim girişimleri açısından ele alındığında; araştırmaların altısında yaşlılık hissi oluşturan simülatörler tercih edilmiştir (9,15,19,22,23,26). İncelenen çalışmaların üçünde orta ve yüksek derecede gerçekliğe yakın insan simülatörleri ile araştırma bulguları elde edilmiştir (16,25,27).…”
Section: Gereç Ve Yöntemlerunclassified